The Role of Platelet in Severe and Fatal Forms of COVID-19 - Esparza-Ibarra, Edgar L.; Ayala-Luján, Jorge L.; Mendoza-Almanza, Brenda; González-Curiel, Irma; Godina-González, Susana; Hernández-Barrales, Marisa; Mendoza-Almanza, Gretel (Current Molecular Medicine, 2022)
On December 31, 2019, the World Health Organization received a report of several pneumonia cases in Wuhan, China. The causative agent was later confirmed as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Since then, the SARS-CoV-2 virus has spread throughout the world, giving rise in 2020 to the 2019 coronavirus (COVID-19) pandemic, which, according to the world map of the World Health Organization, has, until May 18, 2021, infected 163,312,429 people and caused 3,386,825 deaths throughout the world. Most critical patients progress rapidly to acute respiratory distress syndrome (ARDS) and, in underlying form, septic shock, irreversible metabolic acidosis, blood coagulation dysfunction, or hemostatic and thrombotic anomalies have been reported as the leading causes of death due to COVID-19. The main findings in severe and fatal COVID-19 patients make it clear that platelets play a crucial role in developing severe disease cases. Platelets are the enucleated cells responsible for hemostasis and thrombi formation; thus, platelet hyperreactivity induced by pro-inflammatory microenvironments contributes to the
Keywords: cytokine storm